An Inventory Ordering Model with Limited-Time Discount and Service-Level Constraint for Main Distribution Unit (MDU) under Demand Uncertainty - Wicaksono, Ardika Yonatan; Kenaka, Saskia Puspa; Suprayogi, Suprayogi (ITB Graduate School Conference, 2025)
This study proposes a linear optimization model to support inventory ordering decisions during limited-time discount programs under uncertain and dynamic demand conditions. Motivated by operational challenges at PT PLN (Persero), the model addresses fluctuations in customer requests caused by temporary electricity capacity upgrade promotions, which must be fulfilled within a regulated service-level period despite limited stock of Miniature Circuit Breakers (MCBs). The model integrates limited-time pricing policies, deterministic service-level constraints, and a budget-based uncertainty framework to capture demand variability. It introduces price discount abruptness as a parameter to test different price adjustment speeds and analyze their effects on inventory decisions. The objective function aims to maximize profit while minimizing holding and backlog costs. This model provides a practical decision-support tool for utility providers to make responsive and cost-efficient inventory plans without relying on probabilistic demand assumptions.